UJI AKTIVITAS ANTIOKSIDAN DAN INHIBISI ENZIM XANTIN OKSIDASE NANOEMULSI EKSTRAK ETIL ASETAT KULIT BUAH PISANG KEPOK DAN PISANG TANDUK - Devina, Cindy
Based on previous research, ethyl acetate extract from kepok and tanduk banana peels are known to have antioxidant activity. Reduction of extract particle size to nanometer size is expected to increase extract activity. In this study, ethyl acetate extract of kepok and tanduk banana peels were formulated into nanoemulsion. The method used was homogenization using a bath sonicator combined with ultrasonication using a probe sonicator. The best formula consists of 1% w/v extract, 4% w/v oleic acid, Kolliphor RH 40 and Span 80 with a ratio (8: 4)% w/v, and PEG 400 as a cosurfactant as much as 6% b/v. Measurements using Particle Size Analyzer (PSA) gave particle size and polydispersity index for kepok banana nanoemulsion at 90.7 ± 6.46 nm and 0.39 ± 0.01 respectively, while tanduk banana nanoemulsion 80.1 ± 1, 56 nm and 0.35 ± 0.04. Physical stability test results at 3 different temperatures, showed that both nanoemulsions were stable at 4 °C, 25 °C and 40 °C and were stable in the stability testing of freeze and thaw. The results of testing antioxidant activity using the DPPH method proved that nanoemulsion preparations had higher activity than extracts, namely kepok banana peel extract (IC50 27.12 ± 1.86 µg/mL), tanduk banana (IC50 181.19 ± 8.75 µg/mL) and kepok banana nanoemulsion (IC50 2.70 ± 0.28 µg/mL), and tanduk banana nanoemulsion (IC50 0.11 ± 0.03 µg/mL), meanwhile ascorbic acid (IC50 0.85 ± 0.06 µg/mL). IC50 of xanthine oxidase activity of kepok banana peel extract 73.58 ± 0.42 µg/mL and tanduk banana 68.94 ± 1.78 µg/mL, but the activity in both nanoemulsions was not measurable. In this study, it was proven that nanoemulsion formula increased the antioxidant activity of the extract.